ROLE OF CARBON DIOXIDE IN THE DYNAMICS OF MAGMA ASCENT IN EXPLOSIVE ERUPTIONS - Papale P.; Polacci M. (My University, 1999)
The role of carbon dioxide in the dynamics of magma ascent in explosive eruptions is investigated by means of numerical modeling. The model is steady, one-dimensional, and isothermal; it calculates the separated flow of gas and a homogeneous mixture of liquid magma and crystals. The magma properties are calculated on the basis of magma composition and crystal content and are allowed to change along the conduit due to pressure decrease and gas exsolution. The effect of the presence of a two-component (water + carbon dioxide) exsolving gas phase is investigated by performing a parametric study on the CO2/(H2O+CO2) ratio, which is allowed to vary from 0 to 0.5 at either constant total volatile or constant water content. The relatively insoluble carbon dioxide component plays an important role in the location of the volatile-saturation and magma-fragmentation levels and in the distribution of the flow variables in the volcanic conduit. In detail, the results show that an increase of the proportion of carbon dioxide produces a decrease of the mass flow rate, pressure, and exit mixture density, and an increase of the exit gas volume fraction and depth of the fragmentation level. A relevant result is the different role played by water and carbon dioxide in the eruption dynamics; an increasing amount of water produces an increase of the mass flow rate, and an increasing amount of carbon dioxide produces a decrease. Even small amounts of carbon dioxide have major consequences on the eruption dynamics, implying that the multicomponent nature of the volcanic gas must be taken into account in the prediction of the eruption scenario and the forecasting of volcanic hazard.
Keywords: CARBON DIOXIDE; MAGMA ASCENT; EXPLOSIVE ERUPTIONS